New Trends in Economic Behavior: The Phenomenon of the Anti-Usury Movement in Indonesia - Fauzia, Ika Yunia; Riyadi, Abdul Kadir (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
Like any other discourse, ideas regarding usury in Indonesia have evolved over time. This study is concerned with tracing that evolution and with understanding how Indonesian academics, practitioners, and laypersons view the problem. The increasing popularity of usury is then juxtaposed with emergence of anti-usury movements, of which this study identifies 14 throughout the country. Using a phenomenological approach, the study analyses these movements in order to better understand their nature and then categorises them into three classes. The first is that organised by figures affiliated with Hizbut Tahrir Indonesia; the second is initiated by Indonesia’s Salafi ulama; and the third has no clear leadership and membership and is, therefore, somewhat disorganised. The ideas espoused by the anti-usury movement are primarily disseminated via the internet and social media. This study finds that the movement is growing quickly and gaining momentum.